"Robin Hook": The Developmental Effects of Somali Piracy - Anja Shortland (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
Naval counter-piracy measures off Somalia have failed to change the incentives for pirates, raising calls for land-based approaches that may involve replacing piracy as a source of income. This paper evaluates the effects of piracy on the Somali economy to establish which (domestic) groups benefit from ransom monies. Given the paucity of economic data on Somalia, we evaluate province-level market data, nightlight emissions and high resolution satellite imagery. We show that significant amounts of ransom monies are spent within Somalia. The impacts appear to be spread widely, benefiting the working poor and pastoralists and offsetting the food price shock of 2008 in the pirate provinces. Pirates appear to invest their money principally in the main cities of Garowe and Bosasso rather than in the backward coastal communities.
info:eu-repo/grantAgreement/EC/FP7/218105
Keywords: K42; O17; O18; R11; 330; Somalia; piracy; cash transfers; economic development; remote sensing; satellite imaging